2020
DOI: 10.3389/fphar.2020.00358
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets for Combined Therapeutic Strategies to Limit Glioblastoma Cell Migration and Invasion

Abstract: The highly invasive nature of glioblastoma imposes poor prospects for patient survival. Molecular evidence indicates glioblastoma cells undergo an intriguing expansion of phenotypic properties to include neuron-like signaling using excitable membrane ion channels and synaptic proteins, augmenting survival and motility. Neurotransmitter receptors, membrane signaling, excitatory receptors, and Ca 2+ responses are important candidates for the design of customized treatments for cancers within the heterogeneous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 171 publications
(128 reference statements)
3
40
0
Order By: Relevance
“…Both in vitro and invivo, EC cells showed its tropism toward DRG neurons and neuron ber which implied that glutamate receptor signal and neuron-tumor interaction play a signi cant role in EC growth (25). Moreover, in the central nervous system, previous studies demonstrated that the generation of synapse and glutamate receptor signals were linked to the progression of high-grade glioma and breast tumor patients, which corroborates with our results of LGG patients (12,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 90%
“…Both in vitro and invivo, EC cells showed its tropism toward DRG neurons and neuron ber which implied that glutamate receptor signal and neuron-tumor interaction play a signi cant role in EC growth (25). Moreover, in the central nervous system, previous studies demonstrated that the generation of synapse and glutamate receptor signals were linked to the progression of high-grade glioma and breast tumor patients, which corroborates with our results of LGG patients (12,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 90%
“…GB is a very specific type of cancer, as its metastases have rarely been found in other organs, unlike most tumours of epithelial origin that frequently metastasize to the brain [ 55 ]. This seems paradoxical, as GB cells are highly invasive and aggressively infiltrate far into the brain parenchyma, a very early event during GB growth [ 4 , 56 ]. Moreover, updated standard GB treatment protocols [ 7 ] may induce the expression of mesenchymal GB subtypes associated with higher invasiveness [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by distinct histological features such as necrosis, vascular proliferation, and pleomorphism [ 1 ]. Its poor prognosis is due to two major reasons: (1) the diffuse infiltration of highly invasive individual GB cells into the brain parenchyma [ 2 , 3 , 4 ], which prevents complete tumour resection, and (2) the high resilience of brain tumour-initiating cells, i.e., glioblastoma stem cells (GSCs). These cells most likely evolve from normal neural stem cells or by dedifferentiation (reverse differentiation) of any of their progenitors along with the accumulation of oncogenic mutations during gliomagenesis [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of plant-derived bioactive compounds as novel therapeutics may provide therapeutic advantages in HGG research ( Figure 3 , Table 8 ). Around 60 percent of commercially available clinically approved anti-cancer medications are derived from medicinal plants [ 339 , 340 ]. Their multitarget, high selectivity against cancer cells, capable of reducing multidrug chemoresistance, inexpensive and marginal side effects make them valuable potential therapeutics, especially when combined with current therapy advancement [ 341 ].…”
Section: Phytochemicals and Nanoparticles In Hggmentioning
confidence: 99%